Polski międzynarodowy zarobkowy transport samochodowy - szanse, wyzwania, zagrożenia - Brach, Jarosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article describes the situation on the market of the Polish road transport companies - especially changes in the conditions of competition caused by changing of the internal law regulations and EU access, for instance. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 42-52